Early post-operative removal of urethral catheter in patients undergoing colorectal surgery with epidural analgesia – A prospective pilot clinical study. (April 2015) - Coyle, David; Joyce, Kenneth M.; Garvin, Joseph T.; Regan, Mark; McAnena, Oliver J.; Neary, Peter M.; Joyce, Myles R.
Abstract: Background: Urethral catheter (UC) removal is often delayed following colorectal resection due to the perceived increased risk of post-operative urinary retention (POUR) in patients with post-operative epidural analgesia (POEA). We aimed to determine if UC removal at 48 h, irrespective of ongoing POEA use, altered the risk of POUR and other morbidities associated with urethral catheterisation and immobility. Methods: We performed a prospective randomised controlled pilot clinical study. Eligible patients were randomised to an experimental arm, SG1 (UC removal 48 h post-operatively), or a control arm, SG2 (UC removed following cessation of POEA). Rates of POUR, urinary tract infection (UTI), pulmonary complications and surgical site infection (SSI) were recorded. Forty-four patients were recruited (SG1: n = 22; SG2: n = 22). Results: No females developed POUR, while it occurred in three males (20%) in SG1 and 2 males (22.2%) in SG2. All patients who developed POUR had undergone rectal resection. Males in SG1 were not at significantly increased risk of POUR compared to those in SG2 (R.R 0.875, p = 1). No patient developed UTI post-operatively. The rate of pulmonary complications (SG1: n = 2; SG2: n = 3, p = 0.229) and SSI (SG1: n = 5; SG2: n = 2, p = 0.146) were similar between both study arms. Discussion: Males undergoing rectal surgery appear to be at increased risk of developing POUR in the presence of epidural analgesia, independent of the timing of UC removal. Conclusions: All female patients undergoing colorectal resection and male patients undergoing colonic resection may have their urethral catheter removed at 48 h irrespective of use of POEA. Clinical trials registration number: NCT01508767 (http://www.clinicaltrials.gov ). Highlights: We examine the timing of UC removal in colorectal surgery with epidural analgesia. This randomised clinical trial compares early removal with standard timing. The risk of urinary retention is similar in both study arms. Urinary retention only occurred in males undergoing rectal resection. This pilot clinical trial shows early UC removal is safe in females and some males.